2019
DOI: 10.21315/mjms2019.26.5.15
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection, p16INK4a Expression and Genetic Alterations in Vietnamese Cervical Neuroendocrine Cancer

Abstract: Neuroendocrine cervical cancer is a rare subtype of cervical cancer with a highly aggressive malignancy. This study was conducted to analyse the human papillomavirus (HPV) infection and molecular abnormalities in Vietnamese neuroendocrine carcinomas of the uterine cervix. HPV genotyping and p53 mutations were examined using polymerase chain reaction (PCR)-based direct sequencing. Mutations of epidermal growth factor receptor (EGFR), Kirsten rat sarcoma (KRAS), neuroblastoma RAS viral oncogene homolog (NRAS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“… 27 , 28 Therefore, clinical trials exploring the therapeutic effects of PIK3CA/mTOR inhibitors in a subset of NECs are warranted. Similar to our findings, KRAS mutations were previously described in NEC 8 although another recent study 29 confirmed only NRAS but not KRAS mutations in a cohort of 30 NECs. The therapeutic utility of MEK inhibitors in KRAS-mutated NECs remains to be clinically explored.…”
Section: Discussionsupporting
confidence: 93%
“… 27 , 28 Therefore, clinical trials exploring the therapeutic effects of PIK3CA/mTOR inhibitors in a subset of NECs are warranted. Similar to our findings, KRAS mutations were previously described in NEC 8 although another recent study 29 confirmed only NRAS but not KRAS mutations in a cohort of 30 NECs. The therapeutic utility of MEK inhibitors in KRAS-mutated NECs remains to be clinically explored.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, Both of Syn and CD56 were positive in 18 cases(85.7%,18/21),(85.7%,18/21), otherwise, CgA was positive in 9 cases(42.9%,9/21),and the positive staining was more often diffuse than focal. which was similar to previously reported positive rate (19).p16INK4a was diffuse or focally positive in 17 cases (81%,17/21), this was similar with To Van report (20).In their study,p16INK4a overexpression was not found to be correlated with p53 or NRAS mutation,suggested that p16INK4a overexpression was signi cantly correlated with the presence of high-risk HPV strains in neuroendocrine carcinoma of the cervix. Because it may occur in the cervix, p63 can be positive occasionally.…”
Section: Discussionsupporting
confidence: 89%
“…High-risk HPV has been reported to be associated with most cervical cancers, including SCC and ACC. Recent studies have found that NECC is associated with high-risk HPV, mainly HPV16 and HPV18 types ( 50 ). Although HPV18 infection was found to be statistically more common in patients with NECC than in patients with other histological subtypes, no significant differences were found in the mutational profiles of NECC with and without HPV18 ( 11 ).…”
Section: Discussionmentioning
confidence: 99%